Modified Sijunzi Decoction Inhibits Epithelial-Mesenchymal Transition of Non-Small Cell Lung Cancer by Attenuating AKT/GSK3β Pathway in vitro and in vivo - Shao, Niu; Xiao, Yao; Zhang, Jiaxin; Zhu, Yuying; Wang, Shenglong; Bao, Suzhen (Frontiers in Pharmacology, 2022)
Modified Sijunzi Decoction (MSJZD) is an empirical prescription of Traditional Chinese Medicine (TCM) and has been corroborated to be effective in multiple human diseases, but its role in non-small cell lung cancer (NSCLC) is enigmatic. Here we mainly analyze the function and mechanism of MSJZD in NSCLC. In this study, we used a method that coupled ultra-performance liquid chromatography to quadrupole time-of-flight mass spectrometry (UPLC-Q-TOF-MS) to investigate the major constituents in MSJZD with positive and negative ion modes. Additionally, in in vitro experiments, the effects of serum-containing MSJZD on the biological behavior of NSCLC cells induced by TGF-β1 were assessed by cell function experiments. Then, the influences of serum-containing MSJZD on epithelial-mesenchymal transition (EMT)-related markers were examined by immunofluorescence and western blot assays. Also, the AKT/GSK3β pathway and apoptosis-related markers were estimated by western blotting. Tumor xenografts were generated by subcutaneously injecting A549 cells into BALB/c nude mice to determine the effects of MSJZD in vivo. We first analyzed the composition of MSJZD. In positive ion mode, 47 kinds of components were identified. In negative ion mode, 45 kinds of components were identified. We also found that TGF-β1 contributed to inducing cell morphological changes and EMT progression. In vitro, surprisingly, cell proliferation, migration as well as invasion in NSCLC cells induced by TGF-β1, could be weakened by serum-containing MSJZD, and apoptosis was intensified. Moreover, serum-containing MSJZD weakened EMT passage and AKT/GSK3β pathway activation and induced apoptosis-related markers in NSCLC cells triggered by TGF-β1. In vivo, we discovered that MSJZD attenuated the tumor growth, promoted histopathological damage, and induced apoptosis in A549 tumor-bearing mice. Importantly, MSJZD has also restrained the development of EMT, AKT/GSK3β pathway, and TGF-β1 expression levels in nude mice. These findings demonstrated that MSJZD significantly weakened NSCLC progression by modulating EMT and AKT/GSK3β pathway.